Intervenção de terapia de grupo no ciclo vital familiar pós traumatismo cranioencefálico: construção, percepções e viabilidade - Santos, Lyvia de Jesus (2017)
Traumatic brain injury (TBI) is a public health problem with a high morbidity and mortality rate, especially in traffic accidents. It may lead to temporary or permanent sequelae that result in family conflict. Therefore, the objective of this study is to identify the TBI victim and their family caregivers’ perceptions about the process of becoming ill and its influence on the family interactions. The methodological design has adopted a descriptive and interventionist research, with a qualitative approach using an open and mixed process therapy group, based on perspective of Life Cycle Theory. The sample was characterized by family caregivers (n = 10) and victims of TBI (n = 10) attended at the "Resignifying Lives" program (REVIVA) at outpatient clinic of the University Hospital of Sergipe. Two therapy groups were constructed, which discussed themes related to care, daily life and the process of interrelationship in family life and their perceptions, through group dynamics. The results were analyzed through the thematic analysis, grouping them into themes and their respective categories, as follows: 1) TBI patients’ perception about hospitalization and home return; 2) TBI victims family caregivers’ perception about hospitalization and home return; 3) the family life cycle and the challenges in the TBI; 4) therapy group as a strategy to face the challenges in the TBI. Based on the results, it was verified that the family caregiver's experience after TBI affects family stability and causes conflicts, triggers feelings that are adaptive, although with a loss in the family relationship. In addition, the group therapy aided in caring for TBI patients and allowed strategies to be developed to cope with family life. It was concluded that the knowledge built in the groups strengthened the participants' own autonomy, the feeling of belonging, the relief of the anguish, contributed to the reduction of risks, coping with daily difficulties and increasing quality of life. Finally, the group therapy made it possible to understand the manifest way of making visible the difficulties encountered and to seek in the actions the contribution to the development of family life.